Delayed Reperfusion—Coronary Artery Reperfusion Close to Complete Myocardial Necrosis Benefits Remote Myocardium and Is Enhanced by Exercise - Veiga, Eduardo C. A.; Antônio, Ednei L.; Santos, Alexandra A.; Lemes, Brunno; Bocalini, Danilo S.; Picollo, Camila; Levy, Rosely F.; Martins, Flavia L.; Girardi, Adriana Castello Costa; Serra, Andrey J.; Tucci, Paulo J. F. (Frontiers in Physiology, 2019)
The present study aimed to analyze the effects of reperfusion of a distant coronary artery on cardiac function, the ultrastructure, and the molecular environment of the remote myocardium immediately after the completion of myocardial regional necrosis: delayed reperfusion (DR). Additionally, the effects of prior exercise on the outcomes of DR were investigated. Female rats with permanent occlusion or delayed reperfusion were randomly assigned to an exercise (swimming, 1 h/day, 5 days/week for 8 weeks) or sedentary protocol. Thus, the study included the following four groups: sedentary permanent occlusion, exercise permanent occlusion, sedentary delayed reperfusion, and exercise delayed reperfusion. The descending coronary artery was occluded for 1 h. Reperfusion was confirmed by contrast echocardiography, and the rats were observed for 4 weeks. Permanent occlusion and DR caused similar myocardial infarction sizes among the four groups. Interestingly, exercise significantly decreased the mortality rate. Delayed reperfusion resulted in significant benefits, including enhanced hemodynamics and papillary muscle contraction, as well as reduced apoptosis and collagen content. Protein calcium kinetics did not change. Meanwhile, developed tension and the Frank–Starling mechanism were enhanced, suggesting that calcium sensitivity was intensified in myofilaments. Remarkable remote myocardial benefits occurred after distant DR, and prior exercise intensified cardiac recovery. Our findings provide valuable information about DR. Our data might explain the better clinical outcomes in recent studies showing that late reperfusion could improve heart failure in patients with myocardial infarction. In conclusion, DR has remote myocardial benefits, including inotropism enhancement, pulmonary congestion reduction, and collagen and apoptosis attenuation, which are enhanced by prior exercise